A UK perspective on tackling the geoscience racial diversity crisis in the Global North - Dowey, N; Barclay, J; Fernando, B; Giles, S; Houghton, J; Jackson, C; Khatwa, A; Lawrence, A; Mills, K; Newton, A; Rogers, S; Williams, R (Springer Nature, 2021)
Geoscientists will play key roles in the grand challenges of the twenty-first century, but this requires our field to address its past when it comes to diversity and inclusion. Considering the bleak picture of racial diversity in the UK, we put forward steps institutions can take to break down barriers and make the geosciences equitable.